THE INFLUENCE OF EARLY CHILDHOOD EDUCATION ON CHILD DEVELOPMENT AT TK PEMBINA PAGU KEDIRI REGENCY - Sutik; Anik Nuridayanti (Suluh Adiluhung Publisher (SAPub), 2025)
PAUD is an early childhood education that is not attractive to all parents because it is considered a burden and takes up the time of parents. The purpose of this study was to determine the effect of early childhood education on child development at TK Pembina Pagu Kediri Regency. The design of this research is correlational analytic research with cross sectional approach. The population were all children aged 4-5 years of kindergarten class A at TK Pembina Kediri Regency 37 children, using Purposive Sampling technique obtained a sample of 34 respondents. The independent variables studied were PAUD Participation and PAUD Inclusion, while the dependent variable was Child Development. The instrument used was observation. The results were analyzed using the Chi square test (α = 0.05). The results showed that the majority of respondents had developments in the normal category, namely as many as 11 respondents (78.6%) and almost half the respondents had developments in the dubious category, namely as many as 11 respondents (32.4%). Based on data analysis using the Chi square test showed p-value = 0.037 <α = 0.05 then H0 was rejected and H1 was accepted, which means there is an influence of early childhood education on child development at TK Pembina Pagu Kediri Regency. The importance of the role of parents to give decisions to children to attend PAUD programs so that children can develop social intelligence.